2011
DOI: 10.2478/v10191-011-0004-4
|View full text |Cite
|
Sign up to set email alerts
|

Infestation of the pumpkinseed Lepomis gibbosus (Teleostei: Cyprinidae) by the copepod Lernaea Cyprinacea (Crustacea) - some ecological aspects

Abstract: Infestation of the pumpkinseed Lepomis gibbosus (Teleostei: Cyprinidae) by the copepod Lernaea Cyprinacea (Crustacea) - some ecological aspects The copepod Lernaea cyprinacea Linnaeus, 1758 is known by the large spectrum of fish hosts which it infests, and to which it can cause haemorrhages and ulcerations. The paper focuses on some aspects of the relation between the Pumpkinseed sunfish and this copepod: infestation parameters, preferred attaching situs, relationship between the host size and parasiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Sympatrically occurring fish species often show divergent infestation rates by L. cyprinacea. This was linked to several extrinsic and intrinsic factors such as resistance against infection (Shariff and Roberts, 1989;Stavrescu-Bedivan et al, 2014), different trophic behavior (Alam et al, 2012;Iqbal et al, 2012), temperature fluctuations (Raissy et al, 2013;Stavrescu-Bedivan et al, 2014), hydrodynamic conditions (Medeiros and Maltchik, 1999), microhabitat differences (Kadlec et al, 2003;Stavrescu-Bedivan et al, 2014;Innal et al, 2017) or small size (Piasecki et al, 2004;Stavrescu-Bedivan et al, 2011;Innal et al, 2017). Our literature survey revealed that predominantly pelagic fish species were targets of L. cyprinacae, less often small benthic species such as Cobitidae, Cottidae or Gobiidae (e. g. Pónyi and Molnár, 1969;Amin, 1981;Djikanovic et al, 2012;Koyun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sympatrically occurring fish species often show divergent infestation rates by L. cyprinacea. This was linked to several extrinsic and intrinsic factors such as resistance against infection (Shariff and Roberts, 1989;Stavrescu-Bedivan et al, 2014), different trophic behavior (Alam et al, 2012;Iqbal et al, 2012), temperature fluctuations (Raissy et al, 2013;Stavrescu-Bedivan et al, 2014), hydrodynamic conditions (Medeiros and Maltchik, 1999), microhabitat differences (Kadlec et al, 2003;Stavrescu-Bedivan et al, 2014;Innal et al, 2017) or small size (Piasecki et al, 2004;Stavrescu-Bedivan et al, 2011;Innal et al, 2017). Our literature survey revealed that predominantly pelagic fish species were targets of L. cyprinacae, less often small benthic species such as Cobitidae, Cottidae or Gobiidae (e. g. Pónyi and Molnár, 1969;Amin, 1981;Djikanovic et al, 2012;Koyun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Banarescu (1946) found for the first time the anchor worm L. cyprinacea parasitizing L. gibbosus in Romania and the same author provided a detailed list of the pumpkinseed sunfish parasites in 1964 (Banarescu, 1964). More recently, Stavrescu-Bedivan et al (2011) reported the anchor worm from L. gibbosus. Radulescu and Georgescu (1969) studied for the first time the parasites of P. parva in Romanian waters, identifying one protozoan and one nematode species, while Banarescu (1999) cited three protozoan species.…”
Section: > Previous Records Of the Parasite And/or The Host Speciesmentioning
confidence: 99%
“…A number of studies have investigated the differences in parasitism levels of L. cyprinacea on host Cypriniformes species (Gutiérrez-Galindo & Lacasa-Millán, 2005;Barson et al, 2008;Pérez-Bote, 2010;Stavrescu-Bedivan, Popa, Aioanei, & Popa, 2011). In some cases, they can be very abundant: in Chondrostoma orientale Bianco & Banarescu, 1982 from the Kor River Basin, southwestern Iran the prevalence of L. cyprinacea infections reached 100%, with a mean intensity of 10,3 parasites per fish (Sayyadzadeh & Roudbar, 2015), and in Hypophthalmichthys molitrix from Manzala area 64% of the specimens were infected (Nofal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%